Investigating relationships between trait anxiety, emotional processing and psychopathy as a dimensional personality trait - Burns, Sarah Katherine (Curtin University, 2013)
The two goals of this thesis were to validate revised versions of two measures of psychopathy and emotional manipulation, and to test relationships between trait anxiety, emotion processing and psychopathic traits in community samples. Both goals were achieved; the reliability of both the psychopathy and the emotional manipulation measure were improved by adding new items, and trait anxiety and emotion processing was demonstrated to significantly predict both the personality and behavioural aspects of psychopathy.